The meanings of restriction: the Heydt Rescript of 1859 and German migrations to Brazil - Pérez Meléndez, José Juan (História Econômica & História de Empresas, 2024)
On 3 November 1859, the Kingdom of Prussia decreed the so-called Heydt Rescript, a circular that curtailed propaganda and private emigration drives from Prussian lands to Brazil. In line with the assessment of nineteenth-century observers, scholars have long understood the Rescript as a singularly restrictive measure that directly responded to reports of abuse against German colonos culminating in the sharecroppers’ rebellion (revolta dos parceiros) of 1856-1857. However, a number of factors suggest that, beyond Brazil, other Prussian concerns of both a domestic and international political nature motivated the Heydt Rescript. Beginning with the life trajectory of the decree’s author, trade minister August von der Heydt, this article surveys the context that preceded and underpinned the Heydt Rescript in order to show how Prussian military imperatives, economic overtures in Asia, and government changes dovetailed into a multifaceted migration restriction that remained in place until the end of the century.